UPAYA MENINGKATKAN PASSING PERMAINAN SEPAK BOLA MELALUI PENDEKATAN SERCUIT TRAINING ( SISWA KELAS V SDN LIDAH WETAN III 463 SURABAYA ) - Pratama Yudha, Dhiaz; Faridha NurHayati; Indra Bagus Lesmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research background is because student learning outcomes in learning football in Class V students at V SD Negeri lidah wetan III 463 Surabaya Jl. Raya Lidah Wetan No.27, Lidah Wetan, Kec. Lakarsantri, Surabaya, Jawa Timur 60213. students are less enthusiastic about participating in learning, students prefer to wait for the ball to come rather than move after the ball. The aim of this research is to improve student learning outcomes in learning football using a color shooting game approach for Class V students at SD N 222 Gresik. Type of Classroom Action Research carried out in cycle 2. The research subjects were all Class V students of SD N lidah wetan III 463 Surabaya, totaling 34 students, consisting of 12 male students and 22 female students. It can be seen from the percentage of student learning completeness from all aspects in cycle I, namely 61.76%, increasing in cycle II to 76.47%. The completeness of student learning outcomes in each cycle is averaged from the knowledge aspect, attitude aspect and skills aspect. Completeness of learning aspects of knowledge in cycle I was 47.06%, in cycle II it was 76.47%. Completeness of learning the attitude aspect in cycle I was 73.53%, cycle II was 82.35%. Completeness of learning skills aspects in cycle I was 58.82%, cycle II was 82.35%. Increased learning outcomes for each aspect in this research, knowledge aspect 29.41%, attitude aspect 8.82%, skills aspect 23.53%. Based on research results, physical education learning in soccer games using a color shooting game approach can improve student learning outcomes by 14.71%. The suggestions that can be conveyed from this research are that it is hoped that physical education learning using the color shooting game approach can be used as an alternative to improve student learning outcomes in soccer games.